XIX a. pirmosios pusės lietuviškų knygų autoriai - Navickienė, Aušra (Knygotyra, 1997)
During 1795-1864, there were 131 authors of Lithuanian books in Greater Lithuania (they are the main object of our examination). The books of 13 earlier writers were also published, and the literary production of 49 foreign authors was translated into Lithuanian. (The concept "author" in this article is used in a broad sense and includes not only the concrete authors of the books but also compilers, editors, translators, and makers. The concept "book" includes manuscripts and printed works of that time.)The analysis of the biographical facts of the authors shows that in every decade during 1795-1864, about 18 new names commonly appeared. We can speak about a rapid increase in new authors, especially during the third, fifth, and sixth decades of the 19th century. Among the main reasons, we can name an intensive cultural and social life and the sights of the ethnocultural movement.Almost all the Lithuanian authors of that period were born in the territories of ethnographic Lithuania: 54% in the province of Kaunas; 39% in Vilnius; 6% in Suvalkai. The predominance of Žemaičiai (inhabitants of West Lithuania) and their dialect can, in part, be explained by the peculiarity of the Lithuanian educational system and the usage of the Lithuanian language in various regions of the country.The article also deals with the education of Lithuanian authors. 37% of them graduated from priest seminaries, 30% obtained a higher education, 7% had a primary or secondary education, and the education of 26% was obscure. The first authors with secular higher education appeared in the 3rd-4th decades of the 19th century. They produced newly-fashioned ABC books, the first scientific and folk publications, popular brochures about health care, agriculture, housekeeping, and works in the science of language, botany, etc.The profession of the priest was very common and valued during those times in Lithuania. Priests of both confessions (Catholic and Protestant) made up 63% of all authors. The professions of teacher, lawyer, and official were the most popular among secular writers. Those authors made up 27%. (Professions were undetermined for 10% of the authors.)In the modernization process of Lithuanian culture, the first woman author entered the arena of Lithuanian literature. It happened in Greater Lithuania in the sixth decade of the 19th century, forty years earlier than in Minor Lithuania.In this period of seventy years, a new generation of Lithuanian book writers emerged, who essentially renovated the repertoire of Lithuanian literary production and introduced, for the first time, great masterpieces of world literature.